The collection of potato varieties as a reserve of source material for breeding for high yield, earliness, and resistance to diseases and pests - L. I. Kostina; O. S. Kosareva; E. V. Truskinov; T. V. Kirpicheva (Труды по прикладной ботанике, генетике и селекции)
Background. Information is provided about the results obtained by screening the VIR collection of improved potato varieties for main commercial traits: earliness, high yield, high starch content, and resistance to late blight (Phytophthora infestans (Mont.) de Bary), viruses, and pests, such as cyst nematode (Globodera rostochiensis Woll. (Ro1)), and Colorado beetle (Leptinotarsa decemlineata Say).Materials and methods. Potato accessions representing domestic and foreign varieties from the VIR collection served as the material for this research. The screening was performed according to the techniques developed at the Potato Genetic Resources Department of VIR.Results and conclusion. Potato varieties with valuable commercial traits were identified as breeding sources promising for earliness: ‘Bashkirskiy’ (k-25338), ‘Charoit’ (k-25221), ‘Colleen’ (k-25224), ‘Lagun’ (k-25294), etc.; for high yield: ‘Ametist’ (k-25336), ‘Banba’ (k-25222), ‘Bastion’ (k-25198), ‘Nur-Alem’ (k-25253), ‘Senim’ (k-25306), etc.; for high starch content: ‘Charaўnik’ (k-25139), ‘Darnitsa’ (k-25179), ‘Lad’ (k-25180), ‘Maksimum’ (k-25136), etc.; for resistance to late blight: local variety (Georgia) (k-25298, k-25326), ‘Sunkar’ (k-25258), ‘Udovitskiy’ (k-25260), ‘Vektor’ (k-25200), ‘Zvezdochka’ (k-25209); for resistance to viruses: ‘Azart’ (k-25196), Gala (k-25270), ‘Nadezhda’ (k-25213), Utro (k-25219), ‘Volat’ (k-25263), etc. Varieties combining resistance to gold potato cyst nematode with other valuable commercial traits were selected. Varieties with relative resistance to Colorado potato beetle were isolated under favorable conditions for the pest’s development. As a result of the research, new source material was identified, with a potential to improve major commercial traits of potato: earliness, high yield, high starch content, resistance to late blight, viruses, and pests (cyst nematode and Colorado beetle).